Cost effectiveness of two therapeutic regimens of infliximab in ankylosing spondylitis: economic evaluation within a randomised controlled trial. Issue 2 (9th September 2009) - Fautrel, B; Benhamou, M; Breban, M; Roy, C; Lenoir, C; Trape, G; Baleydier, A; Ravaud, P; Dougados, M
Abstract : Objective: To determine the incremental cost-effectiveness ratios (ICERs) of two therapeutic regimens of infliximab for ankylosing spondylitis (AS). Methods: 230 patients with active AS who were participating in a randomised controlled trial comparing two infliximab infusion modalities—every 6 weeks (Q6) and on demand (DEM)—were included in an economic evaluation within the trial. Data were collected by phone every 3 months for 1 year. Direct and indirect costs were calculated from a payer perspective. Health-related quality of life was assessed with a general health rating scale. ICERs were calculated for one 20% improvement (ASAS20), for one partial remission and for one quality-adjusted life year (QALY) gained. Results: The Q6 regimen was significantly more efficacious than the DEM regimen but also more costly (€22 388 vs €17 596; p<0.001), because it required significantly more infliximab infusions per patient (8.4 vs 6.2). The ICERs of the Q6 to DEM regimen were €15 841 for one ASAS20 response, €23 296 for one partial remission and €50 760 for one QALY gained. Conclusion: The administration of infliximab every 6 weeks is cost effective as compared with a DEM regimen; however, the ICER is close to the acceptability threshold of €50 000 for one QALY gained. Trial registration number: NCT 00439283.